STRATEGI GURU PAI DALAM PEMBELAJARAN MENULIS AL-QUR’AN MELALUI METODE DRILL SISWA DI SMPN 1 PULAU HANAUT KABUPATEN KOTAWARINGIN TIMUR - Rahmawati, Siti; Yufina, Auliya (Program Studi PAI STAI Al Falah Banjarbaru, 2024)
Abstract: Realizing that many children can read the Koran but are less able to write the Koran. This is based on interviews with PAI teachers. So PAI teacher strategies are very important in the learning process so that children become enthusiastic about learning to write the Qur'an. This research discusses